Functional neuroimaging in child psychiatry - Ernst, Monique; Rumsey, Judith M. (Current psychiatry reports, 2000)
Functional neuroimaging in child psychiatry presents unique scientific, ethical, and technical challenges. The study of childhood disorders presupposes knowledge of neurodevelopment and brain maturation. However, much of human brain science is based on inferences from animal work and indirect neurochemical measures from body fluids. Neuroimaging can examine brain development directly in humans. The benefits can be enormous for learning how and when to intervene to prevent or treat a disorder. These unprecedented potential gains are countered by complex and difficult ethical issues. Technical advances can reduce ethical concerns by minimizing risks. They also promise to enhance the sensitivity and specificity of the measures (eg, by improving spatial and temporal resolution). Judiciously designed investigations will permit the testing of a priori hypotheses built on rational models of neuropathology. Finally, it is the integration of scientific knowledge across the various fields of neuroscience and clinical research that will push the limits of our understanding of health and disease.